Analytical database of Martian minerals (ADaMM): Project synopsis and Raman data overview. (12th August 2021) - Veneranda, Marco; Sanz‐Arranz, Aurelio; Manrique, Jose Antonio; Saiz, Jesus; Garcia‐Prieto, Clara; Pascual‐Sánchez, Elena; Medina, Jesus; Konstantinidis, Menelaos; Lalla, Emmanuel; Moral, Andoni; Nieto, Luis Miguel; Rull, Fernando; et al.
Abstract: The Mars2020/Perseverance and ExoMars/Rosalind Franklin rovers are both slated to return the first Raman spectra ever collected from another planetary surface, Mars. In order to optimize the rovers scientific outcome, the scientific community needs to be provided with tailored tools for data treatment and interpretation. Responding to this need, the purpose of the Analytical Database of Martian Minerals (ADaMM) project is to build an extended multianalytical database of mineral phases that have been detected on Mars or are expected to be found at the landing sites where the two rovers will operate. Besides the use of conventional spectrometers, the main objective of the ADaMM database is to provide access to data collected by means of laboratory prototypes simulating the analytical performances of the spectroscopic systems onboard the Mars 2020 and ExoMars rovers. Planned to be released to the public in 2022, ADaMM will also provide access to data treatment and visualization tools developed in the framework of the mentioned space exploration missions. As such, the present work seeks to provide an overview of the ADaMM online platform, spectral tools, and mineral collection. In addition to that, the manuscript describes the Raman spectrometers used to analyze the mineral collection and presents a representative example of the analytical performance ensured by the Raman prototypes assembled to simulate the Raman Laser Spectrometer (RLS) and SuperCam systems. Abstract : The Analytical Database of Martian Minerals (ADaMM) provides the scientific community with a comprehensive set of spectroscopic and diffractometric data collected from a wide collection of mineral phases relevant for Mars exploration. As much of the given data have been collected by analytical prototypes emulating the spectroscopic tools onboard ExoMars and Mars 2020 rovers, the ADaMM database is meant as a tool to optimize the scientific output of the data returned from Mars.